Solvent-free organic liquids: an efficient fluid matrix for unexplored functional hybrid materials - Wakchaure, Vivek Chandrakant; Channareddy, Goudappagouda; Babu, Sukumaran Santhosh (Accounts of Chemical Research, 2024)
The invention of solvent-free organic liquids (SOLs) was serendipitous. However, the curiosity-driven research in the later stage delivered new soft materials with exciting optical, and optoelectronic properties along with appealing physical characteristics suitable for the futuristic applications. A slight change in the molecular design resulted in a drastic change in the physical state of molecules demonstrating monomer-like features in the bulk. The basic idea of core isolation has been successful in delivering new SOLs with attractive functional properties. The unique fluid matrix associated with SOLs offers a tremendous opportunity for making hybrid materials by simple mixing. The chance to study the fundamentally important electron transfer, energy transfer, charge transfer interactions, triplet-state emissions, and even detailed NMR experiments in the solvent-free neat state is the major attraction of SOLs. Usually, solvents and their polarity control such molecular properties, and in the case of SOLs, it avoids the use of solvents to study such fundamentally important properties. Besides, SOLs protect the triplet emitters and excited state processes involving triplet states from quenchers and make the analysis possible under ambient conditions. Our effort in this direction was focused on tuning the ground and excited state properties by transforming conventional organic molecules to SOLs and further value addition by preparing the hybrid SOLs. We developed a series of hybrid SOLs, exploring room-temperature phosphorescence, thermally activated delayed fluorescence, charge or energy transfer between donor and acceptor SOLs, selective explosive sensing, etc. A slight variation in the chemical structure or optoelectronic properties of the individual components imparted exciting optical features for the hybrid SOLs. It includes nonemissive charge transfer, tunable emission exciplex, room temperature phosphorescence, and thermally activated delayed fluorescence SOLs. The liquid matrix of donor SOLs accommodated varying amounts of acceptor SOLs to tune the ground and excited state features. In all examples of donor-acceptor-based hybrid SOLs, even a low amount of acceptor, such as a donor-acceptor ratio of 1000:1, can cause pronounced optical properties. Hence, the evaluation of the optical properties of SOLs, especially, in the absence of solvents is so special that it avoids the interference of solvent molecules. Still, the major drawback of SOLs remains unsolved until we report polymerizable SOLs. Although a large variety of SOLs have been reported in the literature, the long-lasting problem of surface stickiness of SOLs was resolved by polymerizable SOLs. It enabled the development of flexible, foldable, and stretchable large-area luminescent films suitable for lighting and display devices. In this Account, we summarize our work on SOLs, hybrid SOLs, polymerizable SOLs, and the application of SOLs in selective sensing of explosives. Finally, an outlook on the feasibility of luminescent polymerizable SOLs in futuristic applications is provided.